2012
DOI: 10.1021/jf303699t
|View full text |Cite
|
Sign up to set email alerts
|

Floral Markers of Cornflower (Centaurea cyanus) Honey and Its Peroxide Antibacterial Activity for an Alternative Treatment of Digital Dermatitis

Abstract: Cornflower (Centaurea cyanus) honey can be characterized by a greenish yellow color and an intense flavor with a bitter aftertaste. Because cornflower honey contains only a limited amount of pollen for the verification of its floral origin, one objective was the characterization of its polyphenol and norisoprenoid contents to assign floral markers. Here, lumichrome (18.8-43.5 mg/kg), 7-carboxylumichrome, (Z/E)-3-oxo-retro-α-ionol, and 3-oxo-α-ionol appeared to be quite suitable for distinguishing cornflower ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Sunflower honey was more frequently chosen by the infected than by the noninfected nurse bees, with a 57 % increase in attractivity in choice tests with honeydew. Its higher antimicrobial activity might be explained by its much higher H 2 O 2 concentration compared to black locust and honeydew honey (Oelschlaegel et al 2012), which was confirmed by the bacterial growth inhibition assay (Fig. 2).…”
Section: Discussionmentioning
confidence: 63%
“…Sunflower honey was more frequently chosen by the infected than by the noninfected nurse bees, with a 57 % increase in attractivity in choice tests with honeydew. Its higher antimicrobial activity might be explained by its much higher H 2 O 2 concentration compared to black locust and honeydew honey (Oelschlaegel et al 2012), which was confirmed by the bacterial growth inhibition assay (Fig. 2).…”
Section: Discussionmentioning
confidence: 63%
“…Honey is not only used as a nutritional product but is also described in traditional medicine as an alternative treatment. Honey and hydrogen peroxide are well-known antibacterial agents, in which the bactericidal activity of honey is attributed to several factors including viscosity, osmolality and the generation of hydrogen peroxide (Oelschlaegel et al, 2012). We selected these two honey samples because they represent the most common and…”
Section: Discussionmentioning
confidence: 99%
“…The bactericidal effect of honey is attributed to its osmolality, acidity and viscosity. However, more recent studies attributed the antibacterial activity of most honey to the hydrogen peroxide generated enzymatically by the action of honey glucose oxidase (GOX) (Brudzynski et al, 2012;Oelschlaegel et al, 2012;Anthimidou et al, 2013), an enzyme that is secreted from the bee's pharyngeal gland . In honey, the GOX enzyme is activated by dilution and the peroxide produced is too mild to cause tissue injury, but it still has antimicrobial activity (Brudzynski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These small-molecular compounds are deciding about taste, dietary and therapeutic value of honeys. The knowledge of the structure and content of volatile compounds in various types of honey might result in a better understanding of honey's flavor and nutrient, as well as-even more important-their therapeutic value [8][9][10][11][12][13]. Investigation of volatile compounds of honey seem to be the right solution, which might help to standardize the quality and authenticity of the product [14].…”
Section: Introductionmentioning
confidence: 99%